Spinal Anaesthesia with Hyperbaric Prilocaine in Day-Case Perianal Surgery: Randomised Controlled Trial - Ozden Gorgoz Kaban; Dilek Yazicioglu; Taylan Akkaya; M. Murat Sayin; Duray Seker; Haluk Gumus (The Scientific World Journal)
Background. The local anaesthetics used in day-case spinal anaesthesia should provide short recovery times. We aimed to compare hyperbaric prilocaine and bupivacaine in terms of sensory block resolution and time to home readiness in day-case spinal anaesthesia. Methods. Fifty patients undergoing perianal surgery were randomized into two groups. The bupivacaine-fentanyl group (Group B) received 7.5 mg, 0.5% hyperbaric bupivacaine + 20 μg fentanyl in total 1.9 mL. The prilocaine-fentanyl group (Group P) received 30 mg, 0.5% hyperbaric prilocaine + 20 μg fentanyl in the same volume. Results. Time to L1 block and maximum block was shorter in Group P than in Group B (Group P 4.6±1.3 min versus Group B 5.9±01.9 min, P=0.017, and Group P 13.2±7.5 min versus Group B 15.3±6.6 min, P=0.04). The time to L1 regression and S3 regression of the sensorial block was significantly shorter in Group P than in Group B (45.7±21.9 min versus 59.7±20.9 min, P=0.024, and 133.8±41.4 min versus 200.4±64.8 min, P<0.001). The mean time to home readiness was shorter for Group P than for Group B (155±100.2 min versus 207.2±62.7 min (P<0.001)). Conclusion. Day-case spinal anaesthesia with hyperbaric prilocaine + fentanyl is superior to hyperbaric bupivacaine in terms of earlier sensory block resolution and home readiness and the surgical conditions are comparable for perianal surgery.